IMPLICATURE AND SOCIAL JUSTICE IN INDONESIAN ENTERTAINMENT SERIES: CONSTRUCTING TOLERANCE THROUGH THE PREMAN PENSIUN SERIES - Setiawati, Beta; Winarti, Winarti (Journal of Pragmatics and Discourse Research, 2026)
This study examines how implicature in the Indonesian television series Preman Pensiun communicates social justice and tolerance values, situating the analysis within broader discourses in Asian media. Drawing on pragmatic theory, particularly Grice’s implicature framework, the research explores how indirect meanings embedded in dialogue convey moral and cultural lessons beyond explicit speech. Data were collected from selected episodes through qualitative discourse analysis, focusing on conversational exchanges highlighting themes of justice, fairness, and tolerance in everyday interactions. The findings reveal that implicatures often emerge through the deliberate flouting of conversational maxims, especially those of relevance and manner, generating hidden moral messages that resonate with audiences. These implicit lessons demonstrate how entertainment media do more than entertain; they actively shape public attitudes and cultural understandings of justice, tolerance, and community life. The representation of masculinity and solidarity in Preman Pensiun reflects local cultural values, particularly regarding authority, cooperation, and morality within Indonesian society. By situating the analysis within discourse studies, this research contributes to scholarship on Asian media by illustrating how popular culture embeds moral discourse within casual communication. At the same time, the study acknowledges its limitations, as the analysis remains largely descriptive. Stronger integration with critical discourse analysis would provide deeper insight into power, ideology, and representation issues, especially regarding gender roles and authority. Future research should expand the dataset, compare similar narrative strategies across Asian television, and explore intersections between local discourse, globalization, religion, and social change.